Eine neue Komplikationsklassifikation in der adulten spinalen Deformitätenchirurgie - Hemmer, Stefan; Al Mansour, Haidara; Pepke, Wojciech; Innmann, Moritz Maximilian; Akbar, Michael (Der Orthopäde, 2018)
BackgroundIn the light of the increasingly aging population and the widespread understanding of the sagittal profile of symptomatic patients with adult spinal deformity (ASD), pervasive utilization of osteotomies on the vertebral column should be expected. These surgeries are accompanied with relatively high complication rates. However, there is no uniform definition or classification in terms of grading the severity or chronological incidence of complications after ASD surgery.ObjectivesThe aim of this work is to give an overview of the different classifications described in the literature hitherto and to propose a standardized, clinically utile classification of complications after ASD surgery. Finally, the aim is to illustrate this classification using two case examples.Materials and methodsWe conducted a systematic PubMed search with the keywords: “adult spinal deformity”, “surgery”, “complications” and “classification”. Results were screened by title, abstract and full-text article.Results22 articles were included in this review. Regarding the systematic classification of the severity of a complication, the CTCAE classification (Common Terminology Criteria for Adverse Events v4.0) is a validated and well-established severity stratification tool used in oncologic treatment.Regarding chronological occurrence, complications can be categorized into three phases: intra-operative, peri-operative and post-operative.DiscussionThe time of occurrence of a certain complication and its severity should constitute the cornerstones of a standardized and practical classification of complications after ASD surgery. To enable uniform reporting and coherent documentation of complications, spine surgeons should find consensus on a standardized classification. Future work needs to be directed towards defining and conducting an individual pre-operative risk stratification of adult spine deformity surgical candidates leading to a possible mitigation of surgery-related complications.